Комунікативні функції передмови як паратексту - Сокол, М. (Питання літературознавства, 2009)
Здійснено компаративний аналіз комунікативних функцій передмови як паратексту. Обґрунтовано, що генезис передмови тісно пов'язаний із таким явищем, як паратекст. Доводиться, що передмова – функціональний комунікативний компонент паратексту, який являє собою доповнення до завершеного літературного твору, якому властивий характер роздумів, особистих визнань та думок автора, висловлваних щодо свого творіння. The article is devoted to the comparative analysis of communicative functions of preface as paratext. In research grounded that genesis of preface, in our view, closely connected with such phenomenon as paratext. In fact prefaces, except for the main paratextual and communicative functions – to lay out basic maintenance, essence, that takes place in work, translation of subject from point of the author, moral resume, address to public, praise and dedication to the well-known people, and give the space to aesthetically important problematic which is actual enough in the literary prefaces of all epochs. Warning a basic event, aesthetic problematic educated a new reader, apt at the mediated forms perception of reality, able to combine various space-temporal realities in the vision, to select major for the time and valuable from the common to all mankind point of view. In this article, it was investigated, that a preface is a functional communicative component of paratext, which shows by itself the adding to the complete literary work, to which peculiar character of reflections, personal confessions and opinions of author, which he expresses in relation to the creation.